Hot EVs – How temperature affects extracellular vesicles - Schulz, Eilien; Karagianni, Anna; Koch, Marcus; Fuhrmann, Gregor (European Journal of Pharmaceutics and Biopharmaceutics, 2020)
In recent years, extracellular vesicles (EVs) and outer membrane vesicles (OMVs) have become an extensive and diverse field of research. They hold potential as diagnostic markers, therapeutics and for fundamental biological understanding. Despite ongoing studies, numerous information regarding function, content and stability of EVs remains unclear. If EVs and OMVs ought to be used as therapeutics and in clinical environments, their stability is one of the most important factors to be considered. Especially for formulation development, EVs and OMVs need to be stable at higher temperatures. To the best of our knowledge, very little work has been published regarding heat stability of neither EVs nor OMVs. In the present study, we investigated B lymphoblastoid cell-derived EVs and OMVs derived from myxobacterial species Sorangiineae as model vesicles. We exposed the vesicles to 37 °C, 50 °C, 70 °C and 100 °C for 1 h, 6 h and 24 h, and also autoclaved them. Interestingly, physico-chemical analyses such as size, particle concentration and protein concentration showed minor alterations, particularly at 37 °C. Flow cytometry analysis emphasised these results suggesting that after heat impact, EVs and OMVs were still able to be taken up by macrophage-like dTHP-1 cells. These data indicate that both mammalian and bacterial vesicles show intrinsic stability at physiological temperature. Our findings are important to consider for vesicle formulation and for advanced bioengineering approaches.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Autoclaving; Drug carriers; Extracellular vesicles; Flow cytometry; Heat stability; Lymphoblastoid cells; Myxobacteria; Outer membrane vesicles